Gellan Gum/Alginate Microparticles as Drug Delivery Vehicles: DOE Production Optimization and Drug Delivery - Henrique Carrêlo; Maria Teresa Cidade; João Paulo Borges; Paula Soares (MDPI AG, 2023)
Gellan gum is a biocompatible and easily accessible polysaccharide with excellent properties to produce microparticles as drug delivery systems. However, the production methods often fail in reproducibility, compromising the translational potential of such systems. In this work, the production of gellan gum-based microparticles was optimized using the coaxial air flow method, and an inexpensive and reproducible production method. A design of experiments was used to identify the main parameters that affect microparticle production and optimization, focusing on diameter and dispersibility. Airflow was the most significant factor for both parameters. Pump flow affected the diameter, while the gellan gum/alginate ratio affected dispersibility. Microparticles were revealed to be sensitive to pH with swelling, degradation, and encapsulation efficiency affected by pH. Using methylene blue as a model drug, higher encapsulation, and swelling indexes were obtained at pH 7.4, while a more pronounced release occurred at pH 6.5. Within PBs solutions, the microparticles endured up to two months. The microparticle release profiles were studied using well-known models, showing a Fickian-type release, but with no alteration by pH. The developed microparticles showed promising results as drug-delivery vehicles sensitive to pH.